2006
DOI: 10.1245/aso.2006.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Results of D2 Versus D3 Gastrectomy (Para-Aortic Lymph Node Dissection) for Advanced Gastric Carcinoma: A Multi-Institutional Study

Abstract: D3 gastrectomy might be beneficial in patients with advanced pN2 gastric cancer within the group with tumors measuring 50 to 100 mm. A randomized controlled trial of patients with 50- to 100-mm tumors should be performed to test the validity of this preliminary result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…Finally, the tumor size was identified as a prognostic factor in the current study. Some previous investigators have also demonstrated a survival benefit of PALN dissection in patients with tumor diameters of 50 to 100 mm, while PALN dissection did not improve the prognosis of patients with a tumor diameter of >100 mm (23). This may be explained by the fact that a predominant recurrence pattern of a very large tumor with serosal exposure might be associated with peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, the tumor size was identified as a prognostic factor in the current study. Some previous investigators have also demonstrated a survival benefit of PALN dissection in patients with tumor diameters of 50 to 100 mm, while PALN dissection did not improve the prognosis of patients with a tumor diameter of >100 mm (23). This may be explained by the fact that a predominant recurrence pattern of a very large tumor with serosal exposure might be associated with peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 93%
“…Carcinomatosis originating from ovarian, colorectal, gastric and pancreatic carcinomas is common, accounting for up to 19% of patients after curative resection of carcinoma and 23-29% of patients with gastric cancer. 1,2 Inflammatory leukocytes massively infiltrate human solid tumors 3 and actively interact with neoplastic cells. The composition and activation status of tumor-infiltrating leukocytes depend on the tumor type and stage as well as on the anatomic location.…”
Section: Introductionmentioning
confidence: 99%
“…Even though no clear benefit has so far been shown, some investigators have pursued a supposed optimum extent of surgical intervention, as in the recently reported evaluation of the possible benefits of extended D2(+) para-aortic lymphadenectomy in patients with potentially curatively resected gastric cancer 18,19,20,21,22,23,24 .…”
Section: Discussionmentioning
confidence: 99%